2022
DOI: 10.12688/hrbopenres.13507.2
|View full text |Cite
|
Sign up to set email alerts
|

Characterising processes and outcomes of tailoring implementation strategies in healthcare: a protocol for a scoping review

Abstract: Background: Tailoring strategies to target the salient barriers to and enablers of implementation is considered a critical step in supporting successful delivery of evidence based interventions in healthcare. Theory, evidence, and stakeholder engagement are considered key ingredients in the process however, these ingredients can be combined in different ways. There is no consensus on the definition of tailoring or single method for tailoring strategies to optimize impact, ensure transparency, and facilitate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In terms of clarifying the core components and functions of tailoring, we feel that with the increasing focus on tailoring, now is an opportune time to synthesize existing examples to see how tailoring is defined and applied. We are engaged in an ongoing scoping review to bring together the available evidence (13), including how tailoring is conceptualized, operationalized, and evaluated, to shed light on some of the hidden trade-offs for researchers and practitioners that are inherent in the process. There may be value in learning from efforts to systematize and categorize different approaches to developing complex interventions (49,65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of clarifying the core components and functions of tailoring, we feel that with the increasing focus on tailoring, now is an opportune time to synthesize existing examples to see how tailoring is defined and applied. We are engaged in an ongoing scoping review to bring together the available evidence (13), including how tailoring is conceptualized, operationalized, and evaluated, to shed light on some of the hidden trade-offs for researchers and practitioners that are inherent in the process. There may be value in learning from efforts to systematize and categorize different approaches to developing complex interventions (49,65).…”
Section: Discussionmentioning
confidence: 99%
“…Since December 2014, when the most recent search for the Cochrane review was published, there appears to be substantial growth in the number of studies focusing on tailored implementation strategies. We conducted an electronic search for key terms ("tailor * " and terms for strategy or intervention and implementation and healthcare) in title and abstracts along with relevant subject headings in MEDLINE (13). In the last 20 years, there has been a clear upward trend in articles referring to tailoring (Figure 1 The 2015 Cochrane review identified substantial variation in tailoring approaches, a lack of detail about how the process was conducted, insufficient rationale underpinning the tailoring process, and no assessment of the relative costs of tailored strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Work stream 3 will be a multiple case study of different tailoring approaches carried out in the individual studies (Goal 4) which will enable us to develop an enhanced understanding of how tailoring works in different service contexts, complementing the findings from the evidence synthesis work. As separate protocol papers on the evidence synthesis workstream are available 20 , 40 we provide more detail on Workstreams 2 and 3 ( Figure 1 ).…”
Section: Protocolmentioning
confidence: 99%
“…More detail is available in the published protocol 20 . In brief, the specific objectives are 1) to determine how tailoring has been defined and conceptualised in healthcare contexts), 2) how it has been operationalised and 3) evaluated.…”
Section: Work Stream 1: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation